La superposición de regímenes jurídicos en el Derecho Internacional para abordar la acidificación de los océanos - Fillol Mazo, Adriana (2022)
The oceans absorb approximately 30% of global CO2 emissions, as they act as carbon sinks along with forests. However, acting as carbon sinks has its consequences, since the oceans are becoming more acidic due to a chemical interaction between water molecules (H2O) and CO2, which produces carbonic acid (H2CO3). Carbonic acid reduces the amount of carbonate ions in the water, which generates a series of negative effects in the marine food chain that affect many marine organisms and therefore also the sea resources from which we obtain food. There is currently no international legal instrument that specifically addresses ocean acidification or its effects on the marine environment. This issue of acidification has implications in many legal sectors of international law, which makes its legal articulation complex, and for this reason there are few works that have dealt with the legal impact of acidification. The general objective of this paper is to analyze, at the universal level, those legal instruments that can be used in the fight against ocean acidification, taking into account that there are two normative regimes with direct implications in this regard: the International Climate Change Regime and the Law of the Sea. Los océanos absorben aproximadamente el 30% de las emisiones globales de dióxido de carbono (CO2), ya que actúan como sumideros de carbono junto a los bosques. Ahora bien, el actuar como sumideros de carbono tiene sus consecuencias, ya que los océanos se están volviendo más ácidos debido a una interacción química entre las moléculas de agua (H2O) y el CO2, que produce ácido carbónico (H2CO3). El ácido carbónico reduce la cantidad de iones carbonato en el agua, lo que genera una serie de efectos negativos en la cadena trófica marina que afectan a muchos organismos marinos y por ende también a los recursos del mar de los que obtenemos alimentos. En la actualidad no hay ningún instrumento jurídico internacional que aborde específicamente la acidificación de los océanos o sus efectos sobre el medio ...